Reduction of Arsenate in a new isolate of Bacillus megaterium (Jahangirnagar University Journal of Biological Sciences, 2020)
In Bangladesh, the ground water of almost all the 64 districts are contaminated with arsenic and in some regions the arsenic concentration is above the World Health Organization’s guideline value. Bioremediation is in demand for its removal from water especially in rural areas. In this study, four soil samples were collected from arsenic contaminated areas of Chandpur, Bangladesh. In total 58 bacterial strains resistant to arsenate were isolated. Among them I-34 has the highest arsenate reducing capability. This bacteria showed resistance to high concentration of arsenite (100 mM) and arsenate (300 mM). Its arsenate reducing enzyme is extracellular and showed highest activity at 60 °C. More interestingly, it showed auto-induction metabolism to produce arsenate reducing enzyme. Molecular characterization by 16S rDNA gene sequence analysis revealed that the bacterium is 100% identical to Bacillus megaterium. I-34 appears to be novel arsenic metabolizing bacteria within this genus. The bacterial isolate can be exploited for the study of possible bioremediation of arsenic containing water and have a potential impact to reduce the arsenate into arsenite form.Jahangirnagar University J. Biol. Sci. 8(2): 47-59, 2019 (December)